1993
DOI: 10.1007/bf01686464
|View full text |Cite
|
Sign up to set email alerts
|

Hexadecylphosphocholine differs from conventional cytostatic agents

Abstract: Alkylphosphocholines, and especially their main representative hexadecylphosphocholine (HPC), show high anticancer activity in methylnitrosourea (MNU)-induced autochthonous rat mammary carcinoma. The regression of MNU-induced rat mammary carcinoma during HPC treatment can be evaluated by computed tomography and sonography. This allows a noninvasive monitoring of therapy in vivo (tumor size, morphology, and blood supply). Both diagnostic modalities can show a rapid concentric decrease in tumor volume as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Alkylphosphocholines (APC) have been proposed as promising membrane targeted antineoplastic drugs, exerting cytotoxic effects in cell culture as well as in animal models (Berger et al, 1993;Clive et al, 1999;Konstantinov and Berger, 1999;Smorenburg et al, 2000;Ruiter et al, 2001). Similar to alkyllysophospholipids, (ALP), APC primarily interfere with cellular membranes without direct interaction with the DNA (Berggren et al, 1993;Bergmann et al, 1994;Berkovic et al, 1995;Zheng et al, 1990;Lucas et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkylphosphocholines (APC) have been proposed as promising membrane targeted antineoplastic drugs, exerting cytotoxic effects in cell culture as well as in animal models (Berger et al, 1993;Clive et al, 1999;Konstantinov and Berger, 1999;Smorenburg et al, 2000;Ruiter et al, 2001). Similar to alkyllysophospholipids, (ALP), APC primarily interfere with cellular membranes without direct interaction with the DNA (Berggren et al, 1993;Bergmann et al, 1994;Berkovic et al, 1995;Zheng et al, 1990;Lucas et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These lipophilic drugs lack bone marrow toxicity and even exert growth stimulatory effects on hematopoietic progenitor cells inducing leukocytosis and thrombocytosis after systemic application (Vehmeyer et al, 1992;Ergezinger et al, 1999;Berkovic et al, 2001). Hexadecylphosphocholine (HePC) represents the first APC used in clinical trials (Miltex R ), (Berger et al, 1993;Clive et al, 1999;Konstantinov and Berger, 1999;Smorenburg et al, 2000). However, because of its gastrointestinal toxicity and its hemolytic side effects, the application of HePC is limited to topical treatment Verweij et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…stimulated interest in this class of compounds previously shown to have antiviral and anticancer activities [79]. Miltefosine is used as a topical agent and has been tested by the oral route in phase I and II clinical trials, which have provided valuable information on human tolerance for the drug [80], The mode of action of this drug is unknown although it presumably interferes with cellular signal transduction [81].…”
Section: Phospholipid Metabolismmentioning
confidence: 99%
“…Two classes of synthetic phospholipid analogues, the alkyllysophospholipids (ALP) as well as the closely related alkylphosphocholines (APC) have been identified that exert potent antineoplastic effects in cell culture and animal models, including brain tumours [229][230][231]. In contrast to most of the antineoplastic drugs in clinical use, these agents primarily interfere with cellular membranes without direct interaction with the DNA.…”
Section: Alkylphosphocholinesmentioning
confidence: 99%